Synchrotron 3D characterization of arrested fatigue cracks initiated from small tilted notches in steel - P. Lorenzino; J.-Y. Buffiere; S. Okazaki; H. Matsunaga; Y. Murakami; H. Matsunaga (Fracture and Structural Integrity)
High resolution synchrotron X-ray tomography has been used to obtain 3D images of arrested cracks initiated at small artificial defects located on the surface of cylindrical steel specimens subjected to mode I fatigue loading. These defects consist in small semi-circular slits tilted at 0¢X, 30¢X or 60¢X with respect to the plane normal to the loading axis; all of them had the same defect size, area = 188 £gm, where the area denotes the area of the domain defined by projecting the defect on a plane normal to the loading axis. Arrested cracks initiated from the notch were observed for all tilt angles at the surface of samples cycled at the fatigue limit (stress amplitude at which the specimen does not fail after 1¡Ñ107 cycles). High resolution synchrotron X-ray tomography has been used to obtain 3D images of those small defects and non-propagating cracks (NPC). Despite the fact that steel is a highly attenuating material for X rays, high resolution 3D images of the cracks and of the initiating defects were obtained (0.65 ƒÝm voxel size). The values of surface crack length measured by tomography are the same as those obtained by optical microscope measurements. The area values present the same tendency as the surface length of NPC, i.e. larger non-propagating cracks areas were observed in the softer steel. In the extreme case of 60o tilted defect, the crack fronts appear much more discontinuous with several cracks propagating in mode I until arrest.